Alcohol's harm to others in Japan: Different rates for different relationships to the drinker in a 2018 national survey. (5th December 2022) - Kinjo, Aya; Kuwabara, Yuki; Fujii, Maya; Okada, Tomomi; Shimogawa, Ko; Minobe, Ruriko; Maesato, Hitoshi; Higuchi, Susumu; Osaki, Yoneatsu
Abstract: Introduction: No study in Japan has investigated alcohol's harm to others (AHTO). Therefore, this study aimed to reveal the situation of AHTO in Japan and examine the factors associated with it based on the relationship with the drinker. Methods: A cross‐sectional population‐based survey was performed in 2018 with 2121 men and 2507 women. Respondents were asked questions about factors such as verbal or physical aggression, being forced to drink alcohol, sexual harassment and their relationship with the drinker. Binomial logistic regression was performed to quantify the associations of AHTO with participants' socio‐demographic status and drinking patterns. Results: The lifetime experience of AHTO was 24.7% for men and 19.3% for women. AHTO from the father and co‐workers were the most common in and outside the home, respectively. The frequency of AHTO from the spouse or co‐workers showed no significant difference for abstainers and drinkers. However, AHTO from the father was more commonly reported among drinkers and those with Alcohol Use Disorders Identification Test scores ≥8 points than abstainers. Of those who experienced AHTO, 24.5% of men and 27.6% of women, and 6.1% of men and 12.9% of women were profoundly affected by it in and outside the home, respectively. Discussion and Conclusions: One in five Japanese residents experienced AHTO in their life, and the characteristics associated with AHTO differed according to the affected individual's relationship with the drinker. Continued monitoring of AHTO and measures aimed at reducing alcohol‐related harm that include AHTO should be promoted.